Exhaled Nitric Oxide in Patients with Stable Chronic Obstructive Pulmonary Disease: Clinical Implications of the Use of Inhaled Corticosteroids - Jo, Yong Suk; Choe, Junsu; Shin, Sun Hye; Koo, Hyeon-Kyoung; Lee, Won-Yeon; Kim, Yu Il; Ra, Seung Won; Yoo, Kwang Ha; Jung, Ki Suck; Park, Hye Yun; Park, Yong-Bum (Tuberculosis and respiratory diseases, 2020)
Fractional exhaled nitric oxide (FeNO) is regarded as a potential biomarker for identifying eosinophilic inflammation. We aimed to evaluate the clinical implication of FeNO and its influence on inhaled corticosteroids (ICS) prescription rate in Korean chronic obstructive pulmonary disease (COPD) patients. FeNO level and its association with clinical features were analyzed. Changes in the prescription rate of ICS before and after FeNO measurement were identified. A total of 160 COPD patients were divided into increased (≥25 parts per billion [ppb], n=74) and normal (<25 ppb, n=86) FeNO groups according to the recommendations from the American Thoracic Society. Compared with the normal FeNO group, the adjusted odds ratio for having history of asthma without wheezing and with wheezing in the increased FeNO group were 2.96 (95% confidence interval [CI], 1.40-6.29) and 4.24 (95% CI, 1.37-13.08), respectively. Only 21 out of 74 patients (28.4%) with increased FeNO prescribed ICS-containing inhaler and 18 of 86 patients (20.9%) with normal FeNO were given ICS-containing inhaler. Previous exacerbation, asthma, and wheezing were the major factors to maintain ICS at normal FeNO level and not to initiate ICS at increased FeNO level. Increased FeNO was associated with the history of asthma irrespective of wheezing. However, FeNO seemed to play a subsidiary role in the use of ICS-containing inhalers in real-world clinics, which was determined with prior exacerbation and clinical features suggesting Th2 inflammation.